2020
DOI: 10.3390/agronomy10040544
|View full text |Cite
|
Sign up to set email alerts
|

Slight Shading Stress at Seedling Stage Does not Reduce Lignin Biosynthesis or Affect Lodging Resistance of Soybean Stems

Abstract: Shade is widespread in agricultural production and affects lignin biosynthesis and lodging resistance of crops. We explored the effects of shade intensity on lignin biosynthesis and lodging resistance at the physiological and molecular levels in two soybean cultivars (Nandou12 and E93) with different shade tolerance under four progressively severe shade treatments, S0-S3 (S0: no shade, S1: slight shade, S2: moderate shade, S3: heavy shade). Our results showed no significant difference in breaking strength of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…Lignin biosynthesis mainly depends upon the multiple enzymatic activities. Among the lot, the PAL enzyme is one of the most important enzymes that plays a role as rate limiting enzyme and catalyst which convert the L-phenylalanine dehydrogenase into trans-cinnamic acid in the shikimic acid pathway [ 76 , 87 ]. CAD is another important enzyme that takes part in the final reaction of the reduction of lignin biosynthesis [ 61 ].…”
Section: Lodging; a Serious Threat To Intercropping Systemmentioning
confidence: 99%
“…Lignin biosynthesis mainly depends upon the multiple enzymatic activities. Among the lot, the PAL enzyme is one of the most important enzymes that plays a role as rate limiting enzyme and catalyst which convert the L-phenylalanine dehydrogenase into trans-cinnamic acid in the shikimic acid pathway [ 76 , 87 ]. CAD is another important enzyme that takes part in the final reaction of the reduction of lignin biosynthesis [ 61 ].…”
Section: Lodging; a Serious Threat To Intercropping Systemmentioning
confidence: 99%
“…Lignin content was determined by using a test kit [51], (Lignin Content Test Kit, Qi Yi, Shanghai) with some modifications. There was a characteristic absorption peak at 280 nm after acetylation for the phenolic hydroxyl group in lignin, and the absorbance of 280 nm was positively correlated with lignin content.…”
Section: Lignin Contentmentioning
confidence: 99%
“…Thus high flexibility of lignin chemical structure to rearrange their bonds is very important to give more compressed materials. Researchers consider lignin as insoluble biopolymers but till now there are many studies regarding lignin chemical structure and biological activity [12].…”
Section: Figurementioning
confidence: 99%
“…They have also demonstrated that using p-toluenesulfonic acid can reach almost completely solubility of lignin at reasonable temperature equal or less than 80 °C and for only 20 min. Figure (12) shows schematic diagram describe the separation process of wood chips components [41].…”
Section: Organosolv Pulping Analytical Processmentioning
confidence: 99%
See 1 more Smart Citation